Calculation of coherent synchrotron radiation using mesh - T. Agoh; K. Yokoya (Physical Review Special Topics. Accelerators and Beams, 2004)
We develop a new method to simulate coherent synchrotron radiation numerically. It is based on the mesh calculation of the electromagnetic field in the frequency domain. We make an approximation in the Maxwell equation which allows a mesh size much larger than the relevant wavelength so that the computing time is tolerable. Using the equation, we can perform a mesh calculation of coherent synchrotron radiation in transient states with shielding effects by the vacuum chamber. The simulation results obtained by this method are compared with analytic solutions. Though, for the comparison with theories, we adopt simplifications such as longitudinal Gaussian distribution, zero-width transverse distribution, horizontal uniform bend, and a vacuum chamber with rectangular cross section, the method is applicable to general cases.